STRATEGI PENCEGAHAN DAN PEMBERANTASAN PENCUCIAN UANG DAN TAHAPAN-TAHAPAN TINDAK PIDANA PENCUCIAN UANG - Kurniati; Mardiyati, Siti (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2022)
Money laundering prevention and suppression strategies rely on presumption of guilt, which means that the person who owns property allegedly derived from a crime must prove that the property does not come from a criminal offence. Theoretically, the principle of probability balance is used to support the reverse proof of the origin of property property.The money-laundering process consists of several steps, such as placement, coating or coating, and integration or merger.